STUDY THE EFFECT OF SPECIFIC CARDIO-VASCULAR EXERCISE ON BMR W.S.R. TO SHARIRA PRAKRUTI (AYUSHDHARA, 2019)
Basic principles of Ayurveda mainly concern with Sharira Kriya, gives knowledge about Dhosh, Dhatu, and Mala etc. According to Ayurvda Prakruti is a factor which originates in a person right from the time of conception and it determines the physical and mental attributes of man. Prakriti, the build and constitution of the human body is a sum total of morphological, physiological and psychological traits of human beings. Prakriti of a man has genetic and acquired aspect; the genetic aspect depends upon Shukra and Shonita, while acquired constitution develops in relation to environmental factors like climate, season, time factor, age, race and individuals (Pratyatmniyta). According to Ayurveda, Prakruti analysis is an important concept, which describes the constituency of a person healthy or diseased. The Prakruti analysis is based on Shareerika and Manasika Gunas. Today, the BMR is used as a measure of an individual's metabolism, which changes with age, weight, height, and a variety of medical conditions. A person's exercise habits may affect their BMR. A daily routine of cardiovascular exercise can improve health and fitness and increase BMR. Exercise and fitness has become an obsession in popular culture hence number of studies were done. The concept of Prakruti plays major role in this regard, hence with an academic interest to know the possible relation of Prakruti, BMR and Cardio-vascular exercise so this topic was undertaken.